Pengaruh Pendekatan Permainan Yang Menyenangkan Terhadap Motivasi Peserta Didik Dalam Pembelajaran PJOK - Suwandi, Muhammad; Ridwan, Mochamad; Muhammad, Heryanto Nur (Prodi Pendidikan Jasmani dan Olahraga, 2026)
Physical Education (PJOK) learning often faces low student motivation due to monotonous conventional approaches. This study analyzed the effectiveness of a fun game approach through quantitative methods with a quasi-experimental one-group pretest–posttest design on 30 students over five weeks. Data were collected using a Likert-scale motivation questionnaire and analyzed using a paired sample t-test. The results showed a 41.09% increase in motivation, from an average of 67.23 to 94.87, with a very large effect size (Cohen's d = 3.42; p < 0.05). Ninety percent of students achieved high motivation after the intervention, compared to only 6.67% at the beginning of the study. The game approach was deemed effective because it was able to fulfill basic psychological needs according to Self-Determination Theory, especially aspects of competence and social relatedness. The integration of game elements such as tiered challenges, healthy competition, team collaboration, and a reward system successfully created a more engaging and enjoyable learning atmosphere. These findings provide practical references for PJOK teachers in designing innovative learning to increase students' motivation and positive attitudes towards physical activity.